Rancang Bangun Sistem Informasi Penilaian Kinerja Karyawan Berbasis Web Pada PSDM Stikom Surabaya - Perwirasari, Isnainul Amanda; Tanuwijaya, Haryanto; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2017)
Stikom Surabaya has 240 employees which consist of official teaching, official doesn't teaching, prodi lecturers, lecturers non prodi, and regular employees. Human Resource Department in Stikom Surabaya (PSDM) is one of supporting factor to improve quality in Stikom Surabaya. Therefore PSDM makes performance appraisal for employees to assess how well their perfomance and it can be reference for next evaluation. However, there is a problem in that process, specifically the sending process evaluation form is inefficiency so it caused PSDM can't monitored directly which department haven't done the evaluation.Information System Web-based Employee Performance Appraisal in PSDM Stikom Surabaya with Graphic Rating Scales (GRS) method made to solve that problem.Performance appraisal with GRS method is using five scales which have been categorized, that scale is used to make conclusion for result in performance appraisal.Result from testing which has been done is Information System Performance Appraisal with Graphic Rating Scales method was compliance with expected demand and it can be used for user. Information System Performance Appraisal has exactly result with manual calculations from excel and it has report for performance appraisal result. Furthermore, PSDM can be monitored which department haven’t done performance appraisal their employee with system directly.Keywords : PSDM, Graphic Rating Scales, Performance Appraisal